IMPLEMENTATION OF E-GOVERNMENT IN PUBLIC SECTOR FINANCIAL ACCOUNTING: DIGITAL-BASED STATE FINANCIAL TRANSPARENCY AND GOVERNANCE - Rizky Pratama Siregar; Annisa Fadillah Nasution; Eka Nurmala Sari (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Digital transformation in state financial management through the implementation of e-government has become a key agenda for bureaucratic reform in Indonesia. This study aims to analyze the implementation of e-government in public sector financial accounting, measure its impact on fiscal transparency, and evaluate the effectiveness of digital-based state financial governance. The study used a mixed methods approach with quantitative analysis of 127 central and regional government agencies and qualitative studies through in-depth interviews. The results show that the implementation of SAKTI (Agency-Level Financial Application System), SPAN (State Treasury and Budget System), and SIMDA (Regional Management Information System) significantly improved the quality of government financial reports, with the transparency index increasing by 47.3% in the 2019–2024 period. However, a digital divide persists between regions, hindering its widespread adoption. This research contributes to the development of an inclusive and sustainable digital financial governance framework.